Exploring the Nature of Seismic Events in the Underground Gas Storages Area of the Volga Federal District - Batugin Andrian; Ogadzhanov Viktor; Han Sergey; Shevchuk Stepan; Kostikov Sergey; Oborin Anton (Russian Journal of Earth Sciences)
Seismicity during UGS operation had not yet been known in Russia. This work presents studies on the manifestation of seismicity in the area of three underground gas storages (UGSs) located in the south-eastern part of the East European Platform (European part of Russia). The tectonic structure of this region, geodynamic conditions and technological characteristics of «Vostochnoye», «Zapadnoye», «Uzhnoye» UGS are presented. An analysis of the situation with the manifestation of seismicity allows us to conclude that it is technogenic in nature, a feature not previously noted on Russian UGSs. There is a wide list of signs indicating the relationship between the mode of operation of UGSs and the nature of seismicity: prior to the start of UGS operation technogenic seismicity in this area was not known; there is a clear correlation between UGS operation and seismicity; the epicenters of seismic phenomena are located in the geodynamic influence zone of the UGS; in the region there are Earth crustal faults that experienced activation in late Cenozoic time and respond to strong earthquakes of neighboring tectonic areas, which consequently indicates their predisposition to reactivation; the change in pressure in the UGS reservoir is sufficient to induce seismicity. The phenomenon of increasing seismic activity during the gas extraction period is noted, which is explained by the effect of softening of the containing massif and its subsequent push-like deformation when the gas pressure in the reservoir is reduced. Despite the weak seismicity, which does not pose a threat to UGS facilities and adjacent territories, it is proposed to include seismic observations in the complex geodynamic monitoring at Russian UGS to establish patterns over a long period of time.